2015
DOI: 10.1088/1367-2630/17/10/103005
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-scale insight into the interactions between hydroxyl radicals and DNA in solution using the ReaxFF reactive force field

Abstract: Cold atmospheric pressure plasmas have proven to provide an alternative treatment of cancer by targeting tumorous cells while leaving their healthy counterparts unharmed. However, the underlying mechanisms of the plasma-cell interactions are not yet fully understood. Reactive oxygen species, and in particular hydroxyl radicals (OH), are known to play a crucial role in plasma driven apoptosis of malignant cells. In this paper we investigate the interaction of OH radicals, as well as H 2 O 2 molecules and HO 2 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 94 publications
(114 reference statements)
3
47
0
Order By: Relevance
“…The ability of H 2 O 2 to produce DNA-strand breaks (alone) was tested over the concentration range relevant to these plasma jets; intriguingly, H 2 O 2 (added as a solution to the MB suspension) did not produce any measureable level of DNA-strand breaks ( figure 4(c)). This result is mirrored in a previous simulation study by Verlackt et al who showed that the OH • directly damages DNA but H 2 O 2 does not [85]. For the plasma treatment parameters investigated in this study, we did not observe a change in the pH or temperature of HEPES directly treated with the plasma jet.…”
Section: Resultssupporting
confidence: 89%
“…The ability of H 2 O 2 to produce DNA-strand breaks (alone) was tested over the concentration range relevant to these plasma jets; intriguingly, H 2 O 2 (added as a solution to the MB suspension) did not produce any measureable level of DNA-strand breaks ( figure 4(c)). This result is mirrored in a previous simulation study by Verlackt et al who showed that the OH • directly damages DNA but H 2 O 2 does not [85]. For the plasma treatment parameters investigated in this study, we did not observe a change in the pH or temperature of HEPES directly treated with the plasma jet.…”
Section: Resultssupporting
confidence: 89%
“…Indeed, OH radicals will have a lower chemical hardness in solution, resulting in an overall lower reactivity towards biomolecules 35 . This behavior has been observed during our peptide impact simulations and also in our earlier studies 22 . However, the purpose of this step was to obtain information on every possible oxidation product, rather than to obtain statistically valid distribution of products.…”
Section: Iii)supporting
confidence: 88%
“…In order to gain knowledge of the processes that occur, insight in the direct interactions between the generated reactive species and the biochemical structures, at the molecular scale, is crucial. To date, a large amount of research has already been performed to better understand these interactions and the subsequent oxidation in the case of lipids, DNA and amino acids [19][20][21][22][23][24][25][26] . However, knowledge involving the interactions of RONS with peptides and proteins remains limited.…”
Section: Introductionmentioning
confidence: 99%
“…In the context of plasma medicine, a number of simulation studies were carried out to obtain atomic‐level insights into the mechanisms of plasma‐biomolecule interactions . By means of reactive molecular dynamics (MD) simulations, including density functional tight‐binding (DFTB), the effect of CAP oxidation on different bio‐surfaces was investigated, such as the interaction of CAP‐generated reactive oxygen species (ROS) with bacterial cell wall components, structural modifications of the skin barrier and P‐glycoprotein induced by OH radicals, as well as their interaction with water, DNA and biofilm components . In general, the interaction of ROS with the above mentioned model systems always leads to the breaking and formation of some bonds, eventually resulting in the modification of these systems, as revealed by the simulations.…”
Section: Introductionmentioning
confidence: 99%